La caducidad en los contratos: caso la caducidad del contrato con la compañía occidental (oxy) - Panchana Ferrin, Suggeidy Laura (2015)
In this paper we analyze the way in which the US oil company failed to comply with the Participation Agreement, which allowed the exploration and exploitation of oil. Occidental (OXY) sued the Ecuadorian State before the International Centre for Settlement of investment Disputes (ICSID), which was not competent to take part in this conflict differences. The Ecuadorian State, to raise and sustain the expiration of the contract with Western oil company managed to recover the sovereignty of its natural resources and forged a historic fact: the recovery of hydrocarbon resources against the might of a multinational entity coming committing irreparable damage, both against the derisory contractual participation clauses, as against the environment, this caused by environmental irresponsibility. Case OXY is an example to be considered by Ecuadorians, Ecuador, Latin American countries and the international community......